Surface plasmonic effect of nanoparticle-like silver nanostructure on the high responsivity of visible/infrared silver-based heterojunction photodetector - Ahmad, Harith; Thandavan, Tamil Many K.; Ismail, Mohammad Faizal (Taylor & Francis, 2019)
The fabrication of a silver (Ag) based photodetector on a silicon dioxide/p-silicon (SiO2/p-Si) substrate using direct current (DC) magnetron sputtering is demonstrated. The proposed method deposits a nanoparticle-like Ag thin film that favours the photoconduction mechanism under light illumination at 468 nm and laser illumination at 660 and 980 nm. The thin film is characterized using scanning electron microscope (SEM), energy dispersive x-ray (EDX), x-ray diffraction (XRD), Raman scattering, photoluminescence (PL) and ultraviolet–visible (UV–VIS) analysis. Current–voltage (I–V) analysis and the calculated rectifying ratio (RR) suggests the establishment of good Schottky contacts for incident light/laser at 468, 660 and 980 nm, with good responsivity towards light and laser illumination in the forward and reverse DC bias regions. The responsivity increases as the wavelength decreases from 980 nm → 660 nm → 468 nm, with the highest responsivity of 213.7 mAW−1 at 468 nm indicating better photoconduction at low light powers. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.